Penerapan Model Pembelajaran Team Games Tournament untuk Meningkatkan Keterampilan Kolaborasi Peserta Didik Kelas V Sekolah Dasar - Dewantari, Oktania; Zainuddin, Almuntaqo; Solekah, Ariyani (FONDATIA, 2024)
This study is a classroom action research that aims to determine the effect of applying the Team Gemes Tournament (TGT) learning model on improving student collaboration skills. This research was carried out in the VA class of SD Muhammadiyah Alam Surya Mentari in the first semester of the 2023/2024 Academic Year with a total of 11 students. This research was conducted in two cycles. The data collection methods in this study are documentation methods, and observation. The collaboration ability of learners is observed through the application of observation methods. The existence of data analysis techniques using quantitative and qualitative data analysis techniques based on increasing the average level of collaboration skills of learners in each cycle serves as an indicator of research success. The results showed that the pre-cycle obtained the average results of student collaboration skills of 49.58% with sufficient criteria, then the first cycle increased by obtaining an average of 68.80% with good criteria, and the second cycle obtained an average of 82.23% with very good criteria. Thus, it can be concluded that the application of the Team Games Tournament (TGT) learning model can improve students' collaboration skills.